Discourses on Citizen Lawsuit as Administrative Dispute Object: Government Administration Law vs. Administrative Court Law (Journal of Indonesian Legal Studies, 2022)
Citizen lawsuit mechanism has been used several times in Indonesian court procedure, although there is no regulation in this matter. The aims of this study were to determine the characteristic of citizen lawsuit in Indonesia, and the expansion meaning of the state administrative decision after the enactment of government administration law, as well as the potential for citizen lawsuit as dispute object of the state administrative court with comparation with serval countries in order to provide an appropriate legal system of citizen lawsuit as ius constituendum. This article used normative legal research with a conceptual approach, legislative approach, and comparative approach. The results indicated that the characteristic of a citizen lawsuit in Indonesia is generally a citizen access to represent the public interest in condition that the state fails to fulfill the rights of its citizen, and the plaintiff does not need to describe the losses he has suffered directly. The expansion of the meaning of state administrative decision under the Government Administrative Law has resulted in the competence of court and the dispute object has been expanded, thus if the citizen lawsuit is viewed from the administrative dispute perspective, it should be included in the State Administrative Court object. However, due to the limited expansion of Article 87 of the Government Administration Law by the Administrative Court Law, both of which are still valid, the State Administrative Court is not authorized to examine and adjudicate citizen lawsuits. Based on comparative data, there are several weaknesses of the citizen lawsuit system such as the legal standing of the applicant/plaintiff which make several countries have changed the provisions of the regulation.